Pancreatic Glucagonoma Metastasising to the Right Ovary Five Years after Initial Surgery: A Case Report - Watt, David Graham; Pandanaboyana, Sanjay; Herrington, Charles Simon; Tait, Iain S (JOP. Journal of the Pancreas, 2013)
Context Glucagonomas of the pancreas are neuroendocrine tumours (NETs) that arise from well-differentiated neuroendocrine cells within the pancreatic islets. They are considered to be aggressive NETs and often have metastases at initial presentation. In contrast localised glucagonoma without metastatic spread may have prolonged disease free survival with radical resectional surgery. Case report The authors present a case of a glucagonoma that initially presented with classical necrolytic migratory erythema and a large solitary mass in the body and tail of the pancreas that was surgically resected. Five years after surgery the patient presented with increased serum glucagon levels and a mass in the right ovary. Pathology of the resected ovary after oophorectomy identified this as an isolated metastatic glucagonoma. Conclusion Glucagonoma is a rare pancreatic NET that has significant malignant potential. This is the first case of a pancreatic glucagonoma metastasising to the ovary 5 years after radical distal pancreatosplenectomy. Image: Dermatosis affecting the axilla.